The Use of Smart Apps Creator-Based Learning Media on Junior High School Students’ Learning Outcomes and Motivation - Egri Izhar Nurfauzan; Nova Elysia Ntobuo; Dewi Diana Paramata; Mursalin Mursalin; Tirtawaty Abdjul; Ratha Doung; Lanto Mohamad Kamil Amali (Universitas Syiah Kuala, 2026)
Science instruction on the topics of global warming and environmental health still faces challenges because the learning process tends to be dominated by conventional methods that are less effective at boosting learning motivation and helping students understand abstract concepts. Therefore, this study aims to analyze the effectiveness of implementing android-based learning media developed using Smart Apps Creator (SAC) on the learning motivation and academic achievement of junior high school students. This study employed a quasi-experimental method with a pretest-posttest design involving an experimental class and a replication class. The study was conducted at SMP Negeri 3 Satap Tabongo with 15 students in the experimental class and at SMP Negeri 3 Kwandang with 23 students in the replication class. Data were collected using pretest and posttest achievement tests, as well as a learning motivation questionnaire using a Likert scale. The results showed that students’ learning motivation was in the “very good” category, with an average percentage of 88.2% in the experimental class and 87.8% in the replication class. Students’ learning outcomes also improved, as indicated by the average pretest and posttest scores. In the experimental class, the average pretest score of 45.73 increased to 84.00 with an N-gain of 0.713 (high category), while in the replication class, the average pretest score of 43.65 increased to 83.13 with an N-gain of 0.706 (high category). The results of the study indicate that android-based learning media developed using SAC is effective in enhancing students’ learning motivation and learning outcomes on the topics of global warming and environmental health. Thus, this medium can serve as an innovative and interactive learning alternative to support science education at the junior high school level